SMART POLICY: MENGADOPSI STRATEGI PEMERINTAH ESTONIA DALAM INDUSTRI KREATIF - Hartika Arbiyanti; Surfian Rahmat AP; Hendika Dwinanda Wicaksana (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
In the digital economy, the creative industry demands agile governance yet often encounters rigid regulatory frameworks. Estonia, a global digital pioneer, offers a "Smart Policy" paradigm that successfully disrupts traditional governance. This study analyzes Estonia's strategy as a model for accelerating creative industry growth. Employing a qualitative literature review, the research synthesizes data from scientific journals and policy papers to map critical success variables. Findings reveal that Estonia's effectiveness rests on three pillars: the XRoad integrated infrastructure, the e-Residency program which removes geographical barriers, and drastic administrative deregulation. This synergy fosters a transparent and efficient business climate. The study concludes that adopting the "Estonia Model" requires more than technology transfer; it necessitates a structural transformation in the bureaucratic mindset. Consequently, this research recommends an adaptive framework for policymakers to establish a sustainable ecosystem for the creative economy